Acute Care Physical Therapy Practice Analysis Identifies the Need for a Core Outcome Measurement Set. Issue 4 (October 2021) - Mayer, Kirby P.; Norris, Traci L.; Kumble, Sowmya; Morelli, Nathan; Gorman, Sharon L.; Ohtake, Patricia J.
Abstract : Purpose: This study's primary objective is to determine the current use of outcome measures (OMs) by physical therapists practicing in acute care settings. Secondarily, this study aims to establish whether physical therapists support the development of a core OM set for use in acute care settings. Methods: An investigator-developed online survey (Qualtrics) was distributed to acute care physical therapy stakeholders, including practicing clinicians, educators, and administrators. The survey contained 4 sections with 28 questions: (1) acute care physical therapy practice patterns; (2) use of OMs in practice; (3) the development of a core OM set; and (4) demographic, education, and experience in the physical therapy profession. Descriptive statistics were used to assess response frequency and rationale for the use of specific OMs. Results: A convenience sample of 170 acute physical therapy stakeholders completed the survey. Respondents represented 38 states, with most respondents (n = 153; 90%) practicing in one or more acute care specialty areas. The majority of respondents (n = 145; 83%) reported using an OM more than 50% of the time in their practice. Physical function was the main construct (n = 163; 96%) respondents assessed with an OM. Acute care physical therapists primarily used OMs to track response to interventions (n = 134; 79%) and develop a care plan (n = 91; 54%). Length of time required to complete an OM and its clinical utility were the most common rationales for selecting an OM (n = 150, 88%; n = 147, 86%, respectively). Strong support was found for developing a core OM set for acute physical therapist practice (n = 147; 86%). The preferred methods for the organization of a core OM set, in rank order, were by diagnosis, International Classification of Functioning, Disability, and Health (ICF) framework, domains of health, and settings/location. Conclusion: Most physical therapists participating in this study of practice in acute care reported using OMs in their daily practice. This survey confirms the desire to develop a core OM set with high clinical utility for use in acute care settings.